ANALISIS PERSEPSI MASYARAKAT MENGENAI KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS BIHBUL - Rengganis, Shabira Arba; Marselina, Resya Dwi (Journal of Information System, Applied, Management, Accounting and Research, 2025)
The quality of health services is an important factor in increasing public trust and satisfaction towards health facilities. This research aims to analyze public perceptions regarding the quality of service at the Bihbul Health Center, Bandung Regency. The research method used is a qualitative approach. Through descriptive analysis method, data collection is obtained through observation, interview, and documentation. The research results show that most of the people are satisfied with the health services provided, especially in the aspects of professionalism of medical personnel and the completeness of facilities. However, there are still several obstacles that need to be fixed, such as long waiting times and less efficient administrative procedures. However, health services at the Bihbul Health Center are still running optimally, and improvement efforts continue to be made to increase public satisfaction.